CSIG-31. ALTERNATIVE RECEPTOR TYROSINE KINASE SIGNALING AS A RESISTANCE MECHANISM TO ERK INHIBITION IN HIGH-GRADE GLIOMAS. (11th November 2019) - Stanton, Ann-Catherine; Koncar, Robert; Golbourn, Brian; Wassell, Michelle; Agrawal, Nishant; Dey, Brittany; Myers, Max; Mack, Stephen; Pollack, Ian; Agnihotri, Sameer
Abstract: Pediatric High-Grade Gliomas (PHGG), which include Diffuse Midline Gliomas (DMG), are a leading cause of brain tumor death in children. Our recent work has identified extracellular signal-regulated kinase 5 (ERK5) as a critical mediator of cell survival in PHGG. Suppression of ERK5 genetically or pharmacologically leads to decreased cell proliferation and increased apoptosis both in vitro and in vivo in multiple PHGG and H3K27M mutant DMG cell lines. Mechanistically, we show that ERK5 directly stabilizes the proto-oncogene MYC at the protein level, providing rationale to clinically target ERK5. ERK5 contains both a kinase domain (KD) and a transactivation domain (TAD), unlike all other ERKs. Unexpectedly, we found that our ERK5 depleted cells could be partially rescued by an ERK5 kinase domain dead (ERK5-KDD) but TAD intact construct. Additionally, persistent ERK5 depletion does not result in complete growth inhibition and therefore we set out to determine potential adaptation or resistance mechanisms in response to ERK5 loss. To address this, we performed RNA sequencing of DMG cells, comparing control cells to ERK5 knockdown cells, and performed gene-ontology (GO) pathway analysis to identify transcriptional changes that occur in response to ERK5 depletion. We identified 105 differentially expressed genes, and GO analysis identified alternative receptor tyrosine kinase (RTK) gene-expression as one of the top biological processes upregulated in response to ERK5 loss. We validated our top targets at the RNA and the protein level. Our top targets were Erb-B2 Receptor Tyrosine Kinase 4 ( ERBB4 ) and Discoidin Domain Receptor Tyrosine Kinase 2 ( DDR2 ), both clinically actionable targets. Our future work will focus on functional validation of these RTKs as potential resistance mechanisms to ERK5 loss. Identification of resistance mechanisms to ERK5 loss will have both biological and translational relevance and may lead to effective therapeutic combinations.